PHYTOPREVENTIVE EFFECT OF BUAH MERAH (Pandanus conoideus Lam.) OIL IN COLITIS-ASSOCIATED CARCINOGENESIS - Oeij Anindita Adhika (Universitas Kristen Maranatha, 2015)
Colorectal cancer has provided a paradigm for the connection between inflammation and cancer. Modulation of intracellular signaling involved in chronic inflammatory response by anti-inflammatory agents represents an important strategy in molecular target-based chemoprevention. The aim of this research is to study the effect of buah merah oil on IL-6 serum level and histopathology of colon in colitis-associated cancer (CAC) mice model. BALB/c mice were randomly divided into four groups. The negative control and buah merah control were given aquabidest and buah merah, respectively, without CAC induction. The AOM/DSS control and buah merah treatment were given azoxymethane (AOM) followed by dextran sulfate sodium (DSS) to induce CAC. The AOM/DSS control was given aquabidest while the buah merah treatment was given buah merah. Data were analyzed by One-Way ANOVA continued with Tukey-HSD. The result showed that IL-6 level in mice administrated with buah merah was significantly lower than the AOM/DSS control (p=0.000). Histopathological analysis scores of colon were analyzed by Kruskal-Wallis continued with Mann-Whitney. The result showed that histopathological analysis score in buah merah treatment was significantly lower than in the AOM/DSS control (p=0.002). Taken together, buah merah oil lowered IL-6 level and histopathological analysis score of colon in CAC mice model. Keywords: CAC, buah merah oil, IL-6 level, histopathological analysis scores of colon